From germ cell specification to gonad formation - Lehmann, Ruth (Henry Stewart Talks, 2008)
Germ cells: the ultimate stem cell, Germ plasm specifies germ cells, The genetics of early Drosophila development: maternal effect mutations, The body pattern of the embryo is preformed during oogenesis by localization of RNA, In Drosophila, the Oskar protein is necessary and sufficient to organize germ plasm, Oskar RNA transport, localization and translation are regulated at many levels, Epigenetic control of early germ cell development, Transcription, Germ cell migration, Wunen, Signaling pathways, The life cycle of germ cells, Growth of the gonad, Genetic analysis of stem cell maintenance and differentiation, Conserved aspects of germ cells
Reviewed at 2018/05/31